Nanjing Gulou Hospital : honoring the heritage and building the future - Jia, Ning; Liu, Weiqi; Cao, Shanshan ([London] : SAGE, 2016)
Early in March 2014, Ding Yitao, the honorary president of Nanjing Gulou Hospital, an affiliated hospital of Nanjing University Medical School, was visiting the outpatient building. Founded in 1892, Gulou Hospital is one of the earliest western medical hospitals constructed in China. Although it was morning peak hour, Ding saw a largely quiet crowd in the outpatient building. In the central part of the hall, a volunteer was playing the piano to soothe patients with music. Ding looked around and felt comfortable with the light blue and turquoise interior decoration. An outdoor water square directly extended into the hall, bringing a hint of calm. This case study considers this hospital and its calming atmosphere.
Originally Published in: Jia, N., Liu, W., & Cao, S. (2015). Nanjing Gulou Hospital: Honoring the Heritage and Building the Future. 6-915-351. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Nanjing Gulou Hospital; Hospitals -- China -- Nanjing (Guangdong Sheng) -- Administration -- Case studies; Business ethics -- China -- Nanjing (Guangdong Sheng) -- Case studies; Organizational behavior -- China -- Nanjing (Guangdong Sheng) -- Case studies